The Effect of High Performance Work System on Intention to Leave and Safety Workarounds: The Role of Burnout as Mediation and Mentoring & Coping Mechanism as Moderator - Syavergio Avia Difaputra; Hunik Sri Runing Sawitri (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the influence of High Performance Work System (HPWS) on intention to leave and safety workarounds, with the role of burnout as a mediation variable and mentoring and coping mechanism as a moderator variable. The study was conducted on non-doctor employees at the Diponegoro National Hospital, Semarang. The method used is a quantitative approach with data collection techniques through questionnaires distributed to respondents. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that HPWS has a negative influence on burnout, which means that the implementation of HPWS can reduce the level of emotional fatigue of employees. In contrast, burnout has a positive effect on intention to leave and safety workarounds, indicating that employees who experience burnout are more likely to want to leave the company and ignore work safety procedures. In addition, burnout acts as a mediator between HPWS and the two variables. Good HPWS implementation is able to reduce burnout, thereby reducing employee intentions to move and increasing compliance with safety procedures. The conclusion of this study is that the effective implementation of HPWS can reduce employee burnout, reduce the desire to leave work, and increase compliance with occupational safety. Mentoring and coping mechanisms play an important role in strengthening the positive effects of HPWS.